A sense of spacing: Toward a diffractive reading of organizational space. Issue 4 (September 2022) - Kuismin, Ari
This article explores how a diffractive methodology can enrich research on organizational space and the senses. Through the creation of interferences, a diffractive methodology directs attention to how differences in sensing are created in the ongoing production of space and what the effects of these are. By using examples from an ethnographic study of the Hub, a university-based entrepreneurship space designed to invoke positive "buzz", the article illustrates how a diffractive methodology allows for the exploration of the sensory design of space and how it governs the possibilities of sensing among participants. The article contributes to organizational research by demonstrating how a diffractive methodology can be utilized to explore sensing as a spatial, unstable achievement and by highlighting how differences in the possibilities of sensing can be an important analytical starting point.